Green synthesis of silver nanoparticles: focus on monosaccharides and fungi isolated from brazilian soil - Cunha, Francisco Afrânio (2016)
Silver nanoparticles (AgNPs) are structures with sizes up to 100 nm and exhibit properties that are different from those found in the bulk material. AgNPs are structures with several technological applications and can be synthetized by chemical, physical and biological methods. Use of microorganisms, sugars, and plants for the biosynthesis of silver nanoparticles is considered a green technology, as it does not involve any harmful chemicals. Among the sugars, monosaccharides (glucose) are promising because they are readily available, inexpensive, and non-toxic. Yeasts have a wide enzymatic range and are easy to handle. However, there are few reports of yeasts with biosynthetic ability to produce stable AgNPs. The waste generated by fungi in AgNP production can be used for catalytic purposes, provided that it is supported on polymer matrices, such as alginate. The objectives of this study were to use glucose and yeasts to produce AgNPs, characterize these structures, and evaluate their antibacterial, antifungal, cytotoxic and catalytic activities. Additionally the waste generated by fungi was used for the production of alginate beads that were used for catalytic purposes. The synthesis of AgNPs was performed with glucose, and sodium dodecyl sulfate (SDS) was used as a stabilizer. The AgNPs of synthetic origin were associated with the antibiotic ciprofloxacin and tested against Escherichia coli. The AgNPs increased the action of ciprofloxacin by 40%. The synergistic action of AgNPs produced with amphotericin B and nystatin against C. parapsilosis was evaluated. Candida spp. were isolated from candidemia of patients admitted to public hospitals in Ceará. AgNPs, when combined with amphotericin B and nystatin, showed potent antifungal activity and increased the zone around the antifungal disk by 222.6 and 319.3%, respectively. The combination of substances AgNPs and amphotericin B or nystatin can potentiate their effects, therefore showing a large zone of growth inhibition. Two yeasts – Rhodotorula glutinis and Rhodotorula mucilaginosa – were isolated from Brazilian soil and their ability to produce AgNPs was evaluated. AgNPs were characterized by UV–vis, DLS, FTIR, XRD, EDX, SEM, TEM and AFM. AgNPs produced by yeasts showed catalytic and antifungal activities. The AgNPs produced by R. glutinis and R. mucilaginosa measured 15.45 nm ± 7.94 and 13.70 nm ± 8.21 (average ± SD), respectively, when analyzed by TEM. The AgNPs showed high catalytic capacity in the degradation of 4-nitrophenol and methylene blue. C. parapsilosis showed high sensitivity to AgNPs and also enhanced the antifungal property of fluconazole (42.2% for R. glutinis and 29.7 % for R. mucilaginosa). Cytotoxic activity of AgNPs was above the concentrations that exerted biological activity, showing the safety of these particles. The alginate spheres produced with these AgNPs of fungal origin were able to degrade 4-nitrophenol and antibiotic ceftazidime, eliminating microbiological action of ceftazidime. Finally, two yeasts isolated from brazilian soil (Ceará), with the ability to produce AgNPs, were described. These particles (AgNPs) showed multifunctionality and can represent a technological alternative in many different areas with potential applications. The use of monosaccharides and yeasts for AgNP synthesis may be an alternative to orthodox synthesis and reduce the environmental impact that these substances cause.